2000
DOI: 10.1152/ajprenal.2000.279.3.f426
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel kidney-specific gene downregulated in acute ischemic renal failure

Abstract: To gain further insights into the molecular mechanisms involved in acute renal failure, we have isolated a new gene from rat and human, named KSP32 (kidney-specific protein with a molecular mass of 32 kDa). KSP32 encodes a novel gene that shows little homology to other mammalian proteins. It, however, shares extensive homology with several proteins found in the nematode Caenorhabditis elegans and plants. The expression of KSP32 mRNA is highly restricted to kidney. In situ hybidization analysis revealed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
(25 reference statements)
1
12
0
Order By: Relevance
“…Previous studies from many laboratories, including ours (2,(22)(23)(24)(25), have reported that MIOX occurs predominantly in the cortical region of the kidney. In the cortex, proximal tubule epithelial cells are responsible for the uptake of the majority of water and nearly all metabolites from the filtrate.…”
Section: Discussionmentioning
confidence: 68%
“…Previous studies from many laboratories, including ours (2,(22)(23)(24)(25), have reported that MIOX occurs predominantly in the cortical region of the kidney. In the cortex, proximal tubule epithelial cells are responsible for the uptake of the majority of water and nearly all metabolites from the filtrate.…”
Section: Discussionmentioning
confidence: 68%
“…8I) would corroborate the data of D-glucoseinduced up-regulation of RSOR͞MIOX. Here, it is worth pointing out a potential paradox that a decreased RSOR͞MIOX expression has been reported in acute renal failure (39), where tubular cells are under extreme oxidant stress (40). It may be that expression of the enzyme depends on the degree or type of oxidant stress (cytosolic vs. membrane vs. mitochondrial); nevertheless, it seems that OxREs are functionally active in RSOR͞MIOX promoter.…”
Section: Discussionmentioning
confidence: 96%
“…The MI has a dynamic role for membrane phosphoinositides in providing for the release of second messengers, such as 1,2 diacylglycerol and inositol triphosphate; therefore, the RSOR, normally expressed in the cortex, conceivably modulates phosphoinositide signaling critical for various cellular events of the renal tubular epithelium. Another recently described gene, designated as kidney-specific protein-32 (KSP32), is also homologous to RSOR (22). The KSR-32 gene was discovered serendipitously in rats with acute renal failure.…”
mentioning
confidence: 99%
“…MIOX is a 32-kDa protein, which was originally identified as mouse renal-specific oxidoreductase (RSOR), has affinity for NADPH, and is also known as kidney-specific protein 32 (KSP-32) (23,29). MIOX expression is up-regulated in diabetes mellitus (23,28), and conceivably, its up-regulation may be responsible for the concomitant MI depletion and increased urinary excretion.…”
mentioning
confidence: 99%